Transformation towards the sustainable management of peatlands: A characterisation of farmers in the Teufelsmoor, Germany - Amelie Hünnebeck‐Wells; Jacqueline Loos; Susanne Abel; Anke Nordt (People and Nature)
Abstract Peatland restoration through rewetting is a pivotal solution to counteract the climate crisis. Since many peatlands with the potential for rewetting are farmland, rewetting can only be achieved in collaboration with peatland farmers. However, the discord between the need to rewet peatlands and the implementation of rewetting measures calls for a transformation in how peatlands are managed. To explore their willingness towards rewetting, interviews were conducted with 19 peatland farmers in the Teufelsmoor, Germany. Here, we categorised the perceptions, challenges and opportunities of rewetting as operational impediments, knowledge and awareness of peatlands and rewetting, collaboration between stakeholders and peatland perceptions and sense of identity. Based on these results, we characterised peatland farmers as Pioneers, Sceptics, Pragmatists and Hobby Farmers. This characterisation showcases peatland farmers as a group with differing perceptions towards rewetting and highlights the need for different approaches to foster a transformation to agriculture that works with peatlands and peatland farmers to ameliorate the climate crisis. Read the free Plain Language Summary for this article on the Journal blog.